Conquering Europe's fruit and vegetable markets - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
African and Caribbean countries pioneered the export of fresh tropical fruits and out-of-season vegetables to Europe 30 years' ego but they have since lost a substantial share of the market to new exporters from Latin America and Asia. Many ACP...